Conversions of 'Bartleby': deconstruction, literature, psychoanalysis. Issue 12 (2nd December 2021) - Gildea, Niall
ABSTRACT: It has become typical for readings of 'Bartleby, The Scrivener' to discuss the many interpretations which have accumulated around the text. A standard move is to point to the similarities between the critic seeking to understand the story, and the story's narrator seeking to understand Bartleby. The critical heritage of 'Bartleby' therefore becomes an ironic spectacle whereby readers fall into a trap signalled bluntly by the text. The irony of the 'Bartleby Industry' has been noted by critics, as has the specific form of its collective error: the conversion of the text and its titular character into other modes of critical interpretation. But are all such conversions equal? Does every analogical reading of 'Bartleby' result in the same critical blindness, or might we make the case for a more nuanced set of results? Might we even think of interpretations which are formally closer to Bartleby than to the narrator? I look at two responses to 'Bartleby', by Adam Phillips and J. Hillis Miller, which explicitly proceed by converting the text to other terms. Through a reading of these analogical approaches I suggest important critical differences, and draw out the relevance of these differences for thinking about this enduringly impassive text.